(untitled) (Comprehensive Journal of Science, 2025)
This review investigates the application of thermodynamic principles to biological systems, emphasizing the human body as a model of an open, self-regulating system. It explores similarities and differences between living organisms and classical thermal machines. The human body continuously transforms chemical energy into mechanical and thermal work, following the same physical laws that govern inanimate systems. By analyzing energy conversion, entropy, and efficiency, this paper demonstrates how thermodynamic principles can deepen our understanding of physiological processes and inspire advancements in medical technology .